Universal amplitude ratios in the three-dimensional Ising universality class - Hasenbusch, Martin (Physical review. B, Condensed matter and materials physics, 2010)
We compute a number of universal amplitude ratios in the three-dimensional Ising universality class. To this end, we perform Monte Carlo simulations of the improved Blume-Capel model on the simple cubic lattice. For example, we obtain A+/A−=0.536(2) and C+/C−=4.713(7), where A± and C± are the amplitudes of the specific heat and the magnetic susceptibility, respectively. The subscripts + and − indicate the high- and the low-temperature phase, respectively. We compare our results with those obtained from previous Monte Carlo simulations, high- and low-temperature series expansions, field theoretic methods, and experiments.